Anticoccidial activity of natural plants extracts mixture against Eimeria tenella: An in vitro and in vivo study - Han, Mingzheng; Hu, Wenfeng; Chen, Tong; Guo, Hanxing; Zhu, Jianfeng; Chen, Feng (Frontiers in Veterinary Science, 2022)
Coccidiosis, an acute epidemic intestinal disease of poultry, is caused by the parasitic protozoan genus Eimeria, with Eimeria tenella being the most pathogenic spp. Novel approaches are required to address the limitations of current treatments for this disease. We investigated the effects of eight plant extracts and essential oils and their mixture on Eimeria tenella as potential treatments for coccidial infection. The anticoccidial effects of non-toxic concentrations of Punica granatum L. (0.005 mg/mL), Plantago asiatica L. (0.780 mg/mL), Bidens pilosa L. (0.390 mg/mL), Acalypha australis L. (0.390 mg/mL), Pteris multifida Poir (0.050 mg/mL), and Portulaca oleracea L. sp. Pl. (0.050 mg/mL) extracts; Artemisia argyi Levl. et Vant. (0.010 μL/mL) and Camellia sinensis (L.) O. Ktze (0.050 μL/mL) essential oils; and their mixture (0.500 mL/mL) on Eimeria tenella were determined using cell viability assays, flow cytometry, and in vivo studies. The eight plant extracts and essential oils and their mixture inhibited Eimeria tenella sporozoites from invading chicken embryo fibroblast cells in vitro. The extract and essential oil mixture improved the feed conversion ratio and body weight gain, reduced fecal oocyst excretion, substantially reduced the mortality of Eimeria tenella-infected chickens, and reduced Eimeria tenella-induced cecal damage in vivo. The results suggest that the extract and essential oil mixtures inhibit Eimeria tenella invasion both in vitro and in vivo, demonstrating their potential as anticoccidial agents.